Vandetanib as a potential new treatment for estrogen receptor‐negative breast cancers. Issue 10 (6th January 2016) - Hatem, Rana; Labiod, Dalila; Château‐Joubert, Sophie; de Plater, Ludmilla; El Botty, Rania; Vacher, Sophie; Bonin, Florian; Servely, Jean‐Luc; Dieras, Véronique; Bièche, Ivan; Marangoni, Elisabetta
Abstract : The receptor tyrosine kinase RET is implicated in the progression of luminal breast cancers (BC) but its role in estrogen receptor (ER) negative tumors is unknown. Here we investigated the expression of RET in breast cancer patients tumors and patient‐derived xenografts (PDX) and evaluated the therapeutic potential of Vandetanib, a tyrosin kinase inhibitor with strong activity against RET, EGFR and VEGFR2, in ER negative breast cancer PDX. The RT‐PCR analysis of RET expression in breast tumors of 446 patients and 57 PDX, showed elevated levels of RET in ER+ and HER2+ subtypes and in a small subgroup of triple‐negative breast cancers (TNBC). The activity of Vandetanib was tested in vivo in three PDX models of TNBC and one model of HER2+ BC with different expression levels of RET and EGFR. Vandetanib induced tumor regression in PDX models with high expression of RET or EGFR. The effect was associated with inhibition of RET/EGFR phosphorylation and MAP kinase pathway and increased necrosis. In a PDX model with no expression of RET nor EGFR, Vandetanib slowed tumor growth without inducing tumor regression. In addition, treatment by Vandetanib decreased expression of murine Vegf receptors and the endothelial marker Cd31 in the four PDX models tested, suggesting inhibition of tumor vascularization. In summary, these preclinical results suggest that Vandetanib treatment could be useful for patients with ER negative breast cancers overexpressing Vandetanib's main targets. Abstract : What's new? Tyrosine kinase receptors have emerged as key targets in breast cancer treatment. Here the authors examine the role of REarranged during Transfection (RET) and epidermal growth factor receptor (EGFR) in estrogen receptor‐negative breast cancers. They show tumor regression induced by the multikinase inhibitor Vandetanib in cancers with high expression of RET or EGFR. In two cohorts of primary breast cancer and patient‐derived xenografts, one third of tumors showed expression of at least one of the two kinase receptors, underscoring Vandetanib's potential as an effective treatment option for estrogen receptor‐negative breast cancers with high expression of RET or EGFR.